2008
DOI: 10.1534/genetics.107.077768
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer Blocking and Transvection at the DrosophilaapterousLocus

Abstract: Intra-and interchromosomal interactions have been implicated in a number of genetic phenomena in diverse organisms, suggesting that the higher-order structural organization of chromosomes in the nucleus can have a profound impact on gene regulation. In Drosophila, homologous chromosomes remain paired in somatic tissues, allowing for trans interactions between genes and regulatory elements on the two homologs. One consequence of homolog pairing is the phenomenon of transvection, in which regulatory elements on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 97 publications
(132 reference statements)
3
33
0
Order By: Relevance
“…Prior genetic analyses have shown that, for many genes, enhancer action in trans is reduced in the presence of a promoter in cis (Martinez-Laborda et al 1992;Casares et al 1997;Gohl et al 2008). Our data are consistent with the model that this reduction results from an enhancer sharing its activity between the two promoters.…”
Section: Cis-and Trans-promoters Compete For Enhancer Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…Prior genetic analyses have shown that, for many genes, enhancer action in trans is reduced in the presence of a promoter in cis (Martinez-Laborda et al 1992;Casares et al 1997;Gohl et al 2008). Our data are consistent with the model that this reduction results from an enhancer sharing its activity between the two promoters.…”
Section: Cis-and Trans-promoters Compete For Enhancer Activitysupporting
confidence: 90%
“…Finally, in light of the extensive pairing in the Drosophila genome, how does an enhancer choose a target promoter when simultaneously presented with promoters in cis and in trans? For several genes, the presence of a promoter in cis reduces the strength of enhancer action in trans (Martinez-Laborda et al 1992;Casares et al 1997;Gohl et al 2008), suggesting that promoters in cis and in trans compete for an enhancer's activity. Because these observations have been largely based on mutant phenotypes in whole animals, the cellular basis for this competition is not yet clear.…”
mentioning
confidence: 99%
“…Thus far, transvection has been observed at all genomic insertion sites tested, suggesting that the Drosophila genome is generally permissive to enhancer action in trans. Furthermore, transgenic experiments have demonstrated that promoters at allelic positions in cis and trans to an enhancer will compete for the enhancer's activity, consistent with earlier classical observations (Geyer et al 1990;Martinez-Laborda et al 1992;Casares et al 1997;Morris et al 1999;Gohl et al 2008). However, enhancer activation of promoters in cis and trans are not equivalent, with enhancers showing a strong preference for a promoter in cis, and frequently showing cell-to-cell variability in the activation of a promoter in trans (Bateman et al 2012a;Mellert and Truman 2012).…”
supporting
confidence: 82%
“…Thus, it is conceivable that enhancers that were scored negatively for transvection in the previous study were, in fact, restricted from acting in trans at detectable levels due to competition from the promoter in cis, whereas other enhancers in the study may have been less sensitive to the promoter in cis. Consistent with this hypothesis, the enhancers of the yellow gene do not appear to act in trans in the presence of a strong promoter in cis (Geyer et al 1990;Morris et al 1999), whereas enhancers from other genes will show low levels of transvection when juxtaposed to a strong cis-promoter and higher levels of transvection in the absence of a cis-promoter (Martinez-Laborda et al 1992;Casares et al 1997;Gohl et al 2008;Bateman et al 2012a;Mellert and Truman 2012). We also found that two enhancers from our study differed in sensitivity to a promoter in cis, as Cre/loxP removal of the LTL promoter increased transvection by the klu enhancer but not by the pax enhancer.…”
mentioning
confidence: 92%
See 1 more Smart Citation